A Methods engineering study on Union Refinery Corporation - Ocampo, Shierly; Daway, Rhey David; Panergo, Mildred; Rodriguez, Federico (College of Engineering, 2004)
The study on Union Refinery Corporation has been conducted to fulfill the main objective of the group which is to apply Methods Engineering in a production system. Applying the knowledge of the techniques and principles of Methods Engineering, the group has identified the problems in the company as well as formulated recommendations for the solutions of the said problems. The problems were further investigated by analyzing the observations made during the company visits and through interviewing the supervisor and workers. The problems determined were divided into four categories, namely materials, man, machine and method. The major problem which is bottleneck in the operation was found to be under the methods category. The causes of this problem were brought by long walks, insufficient capacity of tank for a day production and slow job completion. Major causes of other problems were also identified. It was found, on the other hand, to be under the materials category. These ideals with the limited stocks of bottles near the filling machines and again the insufficient capacity of tank for one day production. The first cause the worker to be idle while the latter cause the major problem. And both cause the worker to suffer the long walks. To account for the major problem cause by slow job completion which is brought by shortage of boxes and non-standard performance due to workers fatigue, the group recommends that the assembly of boxes be done before the start of the operations to eliminates time lost and to avoid machine idle; that the unused rollers be employed at the end of the lines to reduce the fatigue experienced by the worker when lifting boxes which is too high; and that footrests for each operator be installed to eliminates awkward position and at the same time reduce fatigue. For the long walks, it is suggested to relocate the switch of the holding tanks closer to the operators of the line. This way, lost time of operator opening the switch would be eliminated and bottleneck at the previous operator would be avoided.